Intensification of heat transfer in liquid heat exchangers with dimple-pin finning - Trofimov, V. Ye.; Pavlov, A. L. (Technology and design in electronic equipment, 2016)
The authors consider the possibility of intensification of heat transfer in fluid heat exchangers with cavity-pin finning by changing the shape of the cavities. It is shown that the transition from circular to elliptic cavities leads not only to a significant intensification of heat transfer but also reduces the size and weight of the heat exchanger.